Reflections of british society in the campus novel - Žampachová, Irena, 1983- (2006)
The thesis seeks to show the interrelation between society and literature. The reflections of British post-war society in the campus novel are examined in the works of Kingsley Amis, Malcolm Bradbury, and David Lodge